A rasch model approach to gender-based thermal concept analysis in East Java high schools - Fian Rifqi Irsalina; Lina Aviyanti; Renaldy Fredyan (Universitas PGRI Kanjuruhan Malang, 2025)
This research analyzes high school students' understanding of thermal concepts in East Java, focusing on identifying gender-based differences and misconceptions. A descriptive survey with a non-experimental cross-sectional design was conducted using the Thermal Concept Evaluation (TCE) instrument, distributed via Google Forms to 171 students (94 females and 77 males). Data were analyzed using the Rasch model with Winsteps software, providing a detailed diagnosis of student ability levels and item difficulties. The findings revealed significant misconceptions about thermal conductivity and thermal equilibrium, which were challenging for both genders. Male students demonstrated better comprehension of heat transfer and temperature change, while female students showed a slightly higher understanding of boiling concepts. Practical implications include the need for targeted instructional strategies, such as inquiry-based and problem-based learning, incorporating hands-on experiments and technology-based tools like simulations to visualize abstract thermal phenomena. Policymakers and educators are encouraged to adopt conceptual-based curricula, improve laboratory facilities, and provide teacher training programs to address misconceptions and bridge gender gaps in thermal physics education. These strategies aim to enhance students' understanding and prepare them for advanced applications in science and technology.